Development and Evaluation of a Novel Radiotracer 125I-rIL-27 to Monitor Allotransplant Rejection by Specifically Targeting IL-27Rα - Shanshan Zhao; Qian Liu; Feng Gao; Guihua Hou (Molecular Imaging)
Noninvasive monitoring of allograft rejection is beneficial for the prognosis of patients with organ transplantation. Recently, IL-27/IL-27Rα was proved in close relation with inflammatory diseases, and 125I-anti-IL-27Rα mAb our group developed demonstrated high accumulation in the rejection of the allograft. However, antibody imaging has limitations in the imaging background due to its large molecular weight. Therefore, we developed a novel radiotracer (iodine-125-labeled recombinant IL-27) to evaluate the advantage in the targeting and imaging of allograft rejection. In vitro specific binding of 125I-rIL-27 was determined by saturation and competitive assay. Blood clearance, biodistribution, phosphor autoradioimaging, and IL-27Rα expression were studied on day 10 after transplantation (top period of allorejection). Our results indicated that 125I-rIL-27 could bind with IL-27Rα specifically and selectively in vitro. The blood clearance assay demonstrated fast blood clearance with 13.20 μl/h of 125I-rIL-27 staying in the blood after 24 h. The whole-body phosphor autoradiography and biodistribution assay indicated a higher specific uptake of 125I-rIL-27 and a clear radioimage in allograft than in syngraft at 24 h, while a similar result was obtained at 48 h in the group of 125I-anti-IL-27Rα mAb injection. Meanwhile, a higher expression of IL-27Rα was found in the allograft by Western blot. The accumulation of radioactivity of 125I-rIL-27 was highly correlated with the expression of IL-27Rα in the allograft. In conclusion, 125I-rIL-27 could be a promising probe for acutely monitoring allograft rejection with high specific binding towards IL-27Rα on allograft and low imaging background.